2018
DOI: 10.1089/lap.2018.0029
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metal and Plastic Stents for Preoperative Biliary Drainage in Resectable and Borderline Resectable Periampullary Cancer: A Meta-Analysis and System Review

Abstract: The present meta-analysis revealed that metal stents have significantly lower rate of reintervention and cholangitis than plastic stents. But plastic stents have an obvious superiority over metal stents in terms of the incidence of preoperative pancreatitis. More RCTs are required to support this conclusion and provide more detailed information about the complications and treatment. Meanwhile, a uniform standard for the PBD is required in patients with malignant distal biliary obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 28 publications
2
20
3
Order By: Relevance
“…Furthermore, if preoperative drainage is required, the use of a SEMS is favored over a plastic stent, based on the results of two meta-analyses. These concluded that SEMSs were associated with lower rates of endoscopic re-intervention and perioperative cholangitis, despite potentially higher risk of preoperative biliary drainagerelated pancreatitis due to SEMS [137,138].…”
Section: Recommendationmentioning
confidence: 99%
“…Furthermore, if preoperative drainage is required, the use of a SEMS is favored over a plastic stent, based on the results of two meta-analyses. These concluded that SEMSs were associated with lower rates of endoscopic re-intervention and perioperative cholangitis, despite potentially higher risk of preoperative biliary drainagerelated pancreatitis due to SEMS [137,138].…”
Section: Recommendationmentioning
confidence: 99%
“…Self-expandable metallic stents are currently considered the standard of care in line with published data on biliary stent patency. 64…”
Section: Advances In Surgical Management Of Pancreatic Cancermentioning
confidence: 99%
“…It has been shown in previous studies that the frequency of EBD-related pancreatitis was higher in patients with SEMS as compared to plastic stents. 23,30 SEMS and particularly fully covered SEMS could hamper pancreatic duct out flow as compared to plastic stents which could increase the risk of post-ERCP pancreatitis. 31 In this nationwide study, it was not demonstrated that the post-ERCP pancreatitis rate was higher in patients with a SEMS, which was also confirmed by several other studies.…”
Section: Discussionmentioning
confidence: 99%